Macroscopic and microscopic diversity of missplicing in the central nervous system of patients with myotonic dystrophy type 1. Issue 3 (7th February 2018) - Furuta, Mitsuru; Kimura, Takashi; Nakamori, Masayuki; Matsumura, Tsuyoshi; Fujimura, Harutoshi; Jinnai, Kenji; Takahashi, Masanori P.; Mochizuki, Hideki; Yoshikawa, Hiroo
Abstract : Myotonic dystrophy type I (DM1) is a multiorgan disease caused by CTG-repeat expansion in the DMPK gene. Sequestration of the splicing factor MBNL1 results in aberrant splicing in many genes in DM1 skeletal muscle, whereas MBNL2 plays a leading role in missplicing in the central nervous system (CNS) of patients with DM1. Splicing misregulation of most MBNL2-regulated genes occurs in the temporal cortex but not in the cerebellum of autopsied patients with DM1. To understand the diversity at macroscopic and microscopic levels in CNS of patients with DM1. Using autopsied brain tissues, we examined alternative splicing ratios of MBNL2-regulated genes and expression levels of potential splicing factors. We found differences in splicing abnormalities among tested regions of the CNS from patients with DM1. In the frontal and temporal cortices and the hippocampus, many genes were aberrantly spliced, but severity differed among the brain regions. By contrast, there were no significant differences in the ratio of splicing variants for most of the genes in the cerebellar cortex and spinal cord between DM1 and control samples. We failed to find any change in the amount of potential factors (MBNL and CUGBP proteins and DMPK mRNA) which explain the modest missplicing in the cerebellum. LASER capture microdissection demonstrated splicing misregulation in the molecular layer of the cerebellum but not in the granular layer. This is the first study to reveal missplicing in a functional cell layer of DM1 and to compare splicing misregulation in a wide region of the CNS using statistical analysis.